Trends in the development of foreign direct investment with a special view of the Kurdistan region - Iraq for the period (2006-2020) - Majeed, Nagham; Al-Kawaz, Saad; Mohamed Amin, Salah El-Din (Humanities Journal of University of Zakho, 2023)
The importance of our selection and study of this vital topic is to shed light on investment in order to show the impact of the investment environment with its indicators and determinants and its reflection on stimulating economic growth. The totality of the economic, political, legal and administrative conditions that guarantee the safety of its investment and the flow of its returns. The most prominent determinants of the investment environment are (security and political stability, transparency, integrity in administrative transactions, clarity of legal procedures, stability in the exchange rate and inflation rates, bank provision and development, digital environment readiness, economic freedom, human development, and finally globalization) And that the Kurdistan region is part of Iraq that suffers from deficiencies in infrastructure, despite its implementation of projects in the past few years, and it relied on oil as the only source of wealth. Iraq ranked late in international indicators because it is one of the countries with zero economic freedom and an advanced rank in corruption and late globalization, as well as confusion between the central government and the National Investment Commission in creating a favorable investment environment that bears the elements of a successful environment.